Exploring the use of social media for information sharing during the 2014 flood in Malaysia - Tengku Mohd Azzman, Tengku Siti Aisha; Wok, Saodah; A. Manaf, Aini Maznina; Ismail, Rizalawati (2015)
In December 2014, one of the most perilous floods in recent years occurred in Malaysia. The East Coast of Malaysia, including the states of Pahang, Kelantan and Terengganu were areas that were badly affected, and many lost their lives, material possessions, and even homes. The main objective of this paper is to explore the use of social media, and other communication technologies, for example, mobile messaging applications, for the specific purpose of information sharing about the flood in Malaysia. Survey questionnaires were distributed among families directly affected by the flood in East Coast Malaysia (N = 507) in order to examine their use of social media during the flood, and the main source of information used for the purpose of information sharing strategies. The implication in using social media and other communication technologies, as an important and critical source of information during disaster periods in Malaysia will also be discussed. In light of the recent popularity of social media, especially among young adults in Malaysia, this paper could shed light on how social media could be utilized to facilitate relief efforts, or to share critical information during disaster periods, where traditional mainstream media, may not be readily available.